Effectiveness of Educational Calendar on Pregnant Women’s Attitudes Toward Anemia: A Pre-Experimental Study - Audi Nisa Fadila; Ikhwah Mu’minah; Sawitri Dewi; Diah Atmarina Yuliani (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2026)
Background: A high prevalence of anemia in pregnancy has occurred for 2 years in the working area of a Puskesmas Puwrokerto Selatan. Anemia can cause complications during pregnancy. Educational calendars can improve pregnant women’s knowledge and attitudes towards anemia. Objective: To analyze the effectiveness of educational calendars on the attitudes of pregnant women with anemia. Method: This study employed a pre-experimental design with a one-group pretest-posttest type, conducted from March-April 2026 involving 15 pregnant women with anemia determined using a total sampling technique. Instrument used questionnaires and an educational calendar that had been tested for the feasibility of media and materials. Data were analyzed using univariate and bivariate with Paired Sample t-test. Results: The pre-test revealed that 66.67% of participants had good attitudes. After getting an educational calendar intervention for 30 minutes, a posttest conducted on the same day showed an increase to 93.33%, resulting in a difference of 26.67%. Paired sample t-test showed a significance value of p=0.004. Conclusion: Educational calendar effectively improves pregnant woman’s attitudes, with an increase of the mean value of 6.27 and a p-value of 0.004 (<0.05). Educational calendar can be an alternative tool to support efforts in reducing the cases of anemia during pregnancy.